Gran Torino [videorecording (Blu-Ray)] - Lorenz, Robert (Robert B.); Gerber, Bill; Johannson, Dave; Schenk, Nick; Eastwood, Clint, 1930-; Vang, Bee; Her, Ahney; Carley, Christopher (Distributed by Warner Home Video, 2009)
Walt Kowalski is a widower who holds onto his prejudices despite the changes in his Michigan neighborhood and the world around him. Walt is a grumpy, tough-minded, unhappy old man, who can't get along with either his kids or his neighbors. He is a Korean War veteran whose prize possession is a 1972 Gran Torino he keeps in mint condition. When his neighbor, Thao, a young Hmong teenager, becomes pressured by his gang member cousin to steal Walt's Gran Torino, Kowalski sets out to reform the youth. Drawn against his will into the life of Thao's family, Walt is soon taking steps to protect them from the gangs that infest their neighborhood.